#TITLE_ALTERNATIVE# - KHAERUNISA (NIM 10107048); Pembimbing : Prof. Ir. Pudjo Sukarno, M.sc, Ph.D, HASNA
Gas deliverability is the ability of reservoir to deliver gas from reservoir to consumers. One of the main problems is that the amount of gas allocation that is produced does not fulfill the contract time that requested by customers. This is due to decreasing reservoir pressure after production during a certain period of time. At the time when the gas production can no longer fulfill the contract, rearrangement of allocation management should be done. One of the techniques to overcome this problem is to reduce the separator. The purpose of this thesis is to optimize the separator pressure so that the time period of the contract and gas allocation can be fulfilled. Method AOF (Absolute Open Flow) is used to distribute gas rate of each well. Intercept of IPR (Inflow Performance Relationship) and OPR (Outflow Performance Relationship) can be used to determine maximum gas rate that can be delivered by reservoir. The minimum decrease of separator pressure to deliver gas production satisfying contract time is obtained here.